LINC00319-Mediated miR-3127 Repression Enhances Bladder Cancer Progression Through Upregulation of RAP2A - Wang, Xiaoqing; Meng, Ran; Hu, Qing-Mei (Frontiers in Genetics, 2020)
Recent studies suggested that microRNA-3127 (miR-3127) was dysregulated in multiple tumor types and has important roles in tumorigenesis and cancer progression. However, its biological roles and the mechanisms that regulate its expression in bladder cancer (BCA) remain to be determined. The expression level of miR-3127 was measured in BCA tissues and its cellular functions were examined using both in vitro and in vivo experiments. The interaction between miR-3127 and long noncoding RNA (lncRNA) LINC00319 was explored using RNA immunoprecipitation assay and luciferase reporter assays. We showed that miR-3127 expression was significantly downregulated in human BCA tissues and BCA cell lines. Lower miR-3127 levels were associated with worse survival in BCA patients. The overexpression of miR-3127 impaired BCA cell proliferation and invasion, and the knockdown of miR-3127 enhanced BCA cell proliferation and invasion in vitro. Importantly, miR-3127 was able to suppress cell growth in vivo. We demonstrated that miR-3127 repressed the proliferation and invasion of BCA cells though directly targeted the 3′-UTR of RAP2A, which served as a novel oncogene in BCA cells. The suppression of cell proliferation and invasion caused by miR-3127 overexpression could be partially abrogated by ectopic expression of RAP2A. Furthermore, high expression of LINC00319 was correlated with adverse survival in BCA patients. LINC00319 could bind directly with miR-3127 and inhibited its expression, and the tumor-promoting effects of LINC00319 could be reversed by re-expression of miR-3127 in BCA cells. Our findings indicated that lncRNA LINC00319-mediated miR-3127 repression promotes BCA progression through the upregulation of RAP2A. The re-introduction of miR-3127 or inhibition of LINC00319 might represent a promising therapeutic strategy for BCA treatment.